Thermocline Layers Depth and Thickness in Indonesian Waters when Souteast Monsoon - Andreas Bastian Lana; Nia Kurniawati; Noir P. Purba; Mega L. Syamsuddin (Journal Omni-Akuatika, 2017)
Termocline layer is effect of the unstabliized water when its stratified and usually with temperature decrease. This Research comprehensively discussed Indonesian waters, especially at a time when ITF flows strengthened in eastern part of Indonesia as compared to the western waters of Indonesia. Therefore, it is necessary to study the changes in the depth and thickness of the thermocline in various Indonesian waters to determine the condition toward oceanographic phenomenon that occurred in Southeast Monsoon. The data used are secondary data obtained from the World Ocean Atlas the form of climatological data. The data used is the temperature (oC) monthly from year 2005 to 2012 in June-August with a spatial resolution 10. The research location is determined based on the division of zoning Regional Fisheries Management or RFM. Location research adjusted for optimize the benefits of this research in pelagic fishing effort. The method used in this research is the analysis of spatial, temporal, and literature studies about the temperature gradient changes. The result show that Thermocline layer in eastern area of Indonesia found deeper than western Indonesia. Thickness of thermocline layer in western area of Indonesia has lower thickness level rather than eastern area of Indonesia.Keywords : Thermocline, Temperature Gradient, dan South East Monsoon, ITF